Event Related Potentials Index Rapid Recalibration to Audiovisual Temporal Asynchrony - Simon, David M.; Noel, Jean-Paul; Wallace, Mark T. (Frontiers in Integrative Neuroscience, 2017)
Asynchronous arrival of multisensory information at the periphery is a ubiquitous property of signals in the natural environment due to differences in the propagation time of light and sound. Rapid adaptation to these asynchronies is crucial for the appropriate integration of these multisensory signals, which in turn is a fundamental neurobiological process in creating a coherent perceptual representation of our dynamic world. Indeed, multisensory temporal recalibration has been shown to occur at the single trial level, yet the mechanistic basis of this rapid adaptation is unknown. Here, we investigated the neural basis of rapid recalibration to audiovisual temporal asynchrony in human participants using a combination of psychophysics and electroencephalography (EEG). Consistent with previous reports, participant’s perception of audiovisual temporal synchrony on a given trial (t) was influenced by the temporal structure of stimuli on the previous trial (t-1). When examined physiologically, event related potentials (ERPs) were found to be modulated by the temporal structure of the previous trial, manifesting as late differences (>125 ms post second-stimulus onset) in central and parietal positivity on trials with large stimulus onset asynchronies. These findings indicate that single trial adaptation to audiovisual temporal asynchrony is reflected in modulations of late evoked components that have previously been linked to stimulus evaluation and decision-making.